Pengaruh Kualitas Sedimen Dasar Terhadap Karakteristik Lingkungan Keairan, Studi Kasus: Saluran Tarum Barat - Moelyadi Moelyo; Januar Tisa; Bambang Priadie (Balai Teknik Irigasi, 2012)
Erosion and sedimentation are classical problems in water resources management. However, these problems become critical when related with pollution issues of the water environment, due to the increase of human activities and productivity in the catchment area included also the irrigation channels as well as West Tarum Canal that empty into the catchment. Related with the impact to the water environment, the study of characterize of bed sediment pollution becomes more complicated considering the great variety of critical areas, type and source of pollution as heavy metals in an from upper to lower areas of BTB1-BTB 46a. In the context of impact of such pollution, deposition of material pollutants in the West Tarum Canal, WTC bed sediment is selected as case study since pollutants in this canal are structured naturally in the bed sediment and distributed from upper to lower areas. The study methods such as, sediment sampling, pretreatment analysis, laboratory analysis dan data evaluation with the criteria of Japan Environment Quality Stnadar for Soil Pollution (1994). Influence of bed sediment quality to water resources can be significant as indicated by the variety of type, amount and location of pollutants in the WTC bed sediment (mud).